Safety and effectiveness of a novel home-use therapeutic ultrasound device for the treatment of vaginal dryness in postmenopausal women: a pilot study. Issue 4 (8th April 2023) - Hickey, Martha; Baber, Rodney; Eden, John; Brennan, Janelle; Bateson, Deborah; Goldman, Mindy; Rockweiler, Holly; Dreon, Darlene
Abstract : A home-use, therapeutic ultrasound device was safe and effective for treating vaginal dryness after 12 weeks, and effectiveness was maintained to 1 year. Therapeutic ultrasound could offer a new, nonhormone treatment option for postmenopausal women with vulvovaginal atrophy. Abstract: Objective: To evaluate safety and effectiveness of therapeutic ultrasound for treatment of postmenopausal vaginal dryness. Methods: In a pilot study, postmenopausal women with self-reported vaginal dryness were randomized (1:1) to double-blind ultrasound treatment (n = 21) or sham (n = 21) for 12 weeks. Primary effectiveness endpoint was change from baseline to week 12 in Vaginal Assessment Scale symptoms (dryness, soreness, irritation, dyspareunia). Secondary effectiveness endpoint was scoring of clinician-reported Vaginal Health Index (elasticity, fluid, pH, mucosa, moisture). After 12 weeks, participants received open-label ultrasound treatment to 1 year. Safety endpoint was treatment-emergent adverse events. Results: In the modified intent-to-treat population, women showed (mean ± standard error) reduction in Vaginal Assessment Scale with ultrasound treatment versus sham (n = 15, −0.5 ± 0.2 vs n = 15, −0.4 ± 0.3; P = 0.9) and improved Vaginal Health Index (n = 9, 2.7 ± 0.9 vs n = 9, 0.6 ± 1.4; P = 0.3). In the per-protocol analysis population, ultrasound treatment (n = 9) versus sham (n = 8) significantly reduced symptoms score (−0.6 ± 0.3 vs −0.0 ± 1.0; P = 0.4) and significantly improved Vaginal Health Index (2.7 ± 0.9 vs −0.4 ± 1.2; P = 0.03). Improvement in effectiveness endpoints were seen at 1 year compared with baseline. There were no differences in treatment-emergent adverse events between ultrasound treatment versus sham and no serious adverse events. Conclusions: Home-use ultrasound was safe and effective for treating vaginal dryness after 12 weeks. Effectiveness was maintained to 1 year. Therapeutic ultrasound could offer a new, nonhormonal treatment option for postmenopausal women with vulvovaginal atrophy.